Long-wavelength fluorescent boronate probes for the detection and intracellular imaging of peroxynitrite - Sedgwick, Adam C; Han, Hai-Hao; Gardiner, Jordan E; Bull, Steven D; He, Xiao-Peng; James, Tony D (Chemical communications (Cambridge, England), 2017)
Two boronate fluorescent probes have been developed for the detection of peroxynitrite ( TCFB1 and TCFB2 ). TCFB1 was shown to have a low sensitvity towards peroxynitrite and have a poor solubility in aqueous solution whereas TCFB2 demonstrated high sensitivity towards peroxynitrite and mitochondria localisation with the ability to detect exogenous and endogenous peroxynitrite in live cells (Hep-G2, RAW 264.7, HeLa and A459). Two boronate fluorescent probes have been developed for the detection of peroxynitrite ( TCFB1 and TCFB2 ).